2019
DOI: 10.3389/fendo.2019.00377
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hormone Replacement Therapy on Bone Mineral Density and Body Composition in Chinese Adolescent and Young Adult Turner Syndrome Patients

Abstract: A longitudinal observational study was performed comparing BMD and body composition in Turner syndrome girls before and after 1 year of HRT treatment. Whole body BMD, femur neck BMD, total hip BMD, and lean mass were significantly increased, but there was no difference in fat mass, and lumbar spine BMD. Purpose: Low bone mineral density (BMD) is one of the major health problems in Turner syndrome (TS) patients, and a certain percentage of TS girls are treated with hormone replacement th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Current studies have found that decreased HL and BMD increase the risk of fracture in women with TS ( 54 , 55 ), while no study has confirmed that decreased BMD in women with TS increases the risk of HL. Previous studies have found that HRT can effectively improve the BMD levels of the whole body, femoral neck and hip in TS patients ( 56 ). In this study, it was found that after HRT in TS patients, there was no statistical difference in BMD between the normal hearing group and the hearing loss group, suggesting that HRT can improve BMD of patients to a certain extent, but there was no significant improvement in hearing level of patients.…”
Section: Discussionmentioning
confidence: 96%
“…Current studies have found that decreased HL and BMD increase the risk of fracture in women with TS ( 54 , 55 ), while no study has confirmed that decreased BMD in women with TS increases the risk of HL. Previous studies have found that HRT can effectively improve the BMD levels of the whole body, femoral neck and hip in TS patients ( 56 ). In this study, it was found that after HRT in TS patients, there was no statistical difference in BMD between the normal hearing group and the hearing loss group, suggesting that HRT can improve BMD of patients to a certain extent, but there was no significant improvement in hearing level of patients.…”
Section: Discussionmentioning
confidence: 96%
“…The study's authors emphasized the need for long-term investigations to determine whether this effect persists after discontinuing rhGH therapy. Abdominal obesity, strongly linked to insulin resistance and MetS features, is notably prevalent in adult women with TS, with greater fat mass assessed through dual-energy X-ray absorptiometry (DXA) or magnetic resonance imaging (MRI) [38,39]. In contrast, adolescents with TS did not show significant differences in total body weight and VF compared to the control group [13].…”
Section: Discussionmentioning
confidence: 99%
“…However, the limitations of this method should be taken into account. One of the disadvantages is the influence of body size on areal BMD interpretation, which is important in the case of TS patients [ 14 ]. Therefore, one of the studies selected for our meta-analysis estimated another parameter—bone mineral apparent density (BMAD).…”
Section: Methodsmentioning
confidence: 99%